ANALISIS PROSES REKRUTMEN DAN SELEKSI PADA KARYAWAN PT. SWABINA GATRA GRESIK - Prawesti, Fadila Galih; Amalina Rizqi, Maulidyah (Jurnal Bisnis dan Kewirausahaan, 2024)
This exploration was led to figure out how the Worker Enrollment and Choice Cycle at PT Swabina Gatra Gresik, figure out the impediments and elective arrangements in tackling issues. Information assortment methods through perception and meetings, in particular straightforwardly noticing the item being considered. In view of the aftereffects of the conversation, it shows that the Representative Enlistment and Determination process at PT Swabina Gatra Gresik is as per the standard jobs and specialists given overall. The obstructions that happen are the distance of the spot or unit that is a long way from the administrative center, the limit of qualified HR in a few position regions. Arrangements did incorporate leading internet based interviews by means of zoom meeting or google meet, help from the preparation unit so these workers can find their weaknesses and enter the rules.